Simulator sickness and the Simulator Sickness Questionnaire in Polish practice. A study involving professional drivers subject to compulsory initial and periodic qualification courses - Marcin Cybulski; Piotr Rzeźniczek; Bartosz Bilski (Nofer Institute of Occupational Medicine, 2020)
Background A phenomenon of simulator sickness is measurable in terms of physiological symptoms. The article presents the practical use of the Simulator Sickness Questionnaire (SSQ) in post-exposure research, together with feedback given by the examined drivers. Material and Methods The study was conducted on the AutoSim AS 1600 simulator, and involved 130 drivers attending preliminary and periodic qualification courses in road transportation. The following tools were used throughout the research: the SSQ by Kennedy et al., translated into Polish by Biernacki et al. (with symptoms including nausea, oculomotor disturbances & disorientation symptoms, and the SSQ total), and a tool evaluating the SSQ (comprehensibility and time consumption on a 1-6 scale). Results In the study group (N = 130), some statistically significant differences in the SSQ results were observed. Among younger drivers ( 29.5 years old) - the disorientation symptoms after simulation. The length of sleep and the quality assessment of the conducted task were higher in the asymptomatic groups. Also, the results indicate a positive reception of the tool by the examined individuals (N = 113), with time consumption marked as low (M = 2.44 on a 1-6 scale) and comprehensibility as high (M = 5.62 on a 1-6 scale). Conclusions The research indicates the occurrence of simulator sickness symptoms even in simulators, which accurately reflect vehicle movements. The feedback given by the examined individuals, together with the level of involvement in the SSQ use, indicates a positive reception of the tool. Med Pr. 2020;71(1):47-58